Psychological distress and psychosocial care in adults with glaucoma in Africa: A systematic review protocol - Chelsea Charlyne Kosoku; Albert Kwadjo Amoah Andoh; Constance Kukuaa Akuffo; Josephine Ampong; Nana Akwasi Owusu Mensah; Kwesi Sewe; Isaiah Osei Duah; Alexander K. Schuster; Simon Christoph König; Kwadwo Owusu Akuffo (PLoS ONE, 2026)
A diagnosis of glaucoma often carries a substantial psychological burden. The chronic nature of the disease, the prospect of lifelong treatment, the possibility of surgery, and concerns about progressive vision loss can contribute to significant psychological distress. Despite growing recognition of these emotional challenges, there has been no systematic synthesis of the burden of psychological distress among adults with glaucoma in Africa or of the psychological support services available within glaucoma care. This protocol, registered with the International Prospective Register of Systematic Reviews (PROSPERO: CRD420261338962), outlines a systematic review designed to address this gap. The review will comprehensively assess the prevalence and determinants of psychological distress among adults with glaucoma and identify interventions or support services integrated into glaucoma care across African settings. Searches will be conducted in PubMed, Scopus, CINAHL, Google Scholar, and African Journals Online without language or date restrictions. Retrieved records will be managed in EndNote and screened in Covidence by two independent reviewers, with disagreements resolved through consensus or consultation with a senior reviewer. Risk of bias and methodological quality will be evaluated using established critical appraisal tools. Where sufficient data are available, findings will be synthesized through meta-analysis; otherwise, a structured narrative synthesis following synthesis-without-meta-analysis principles will be undertaken. By consolidating the available evidence, this review aims to inform the integration of psychological care into glaucoma management and support more holistic approaches to preserving both visual and mental well-being.